Filozofia fizyki teoretycznej Einsteina i Diraca - Staruszkiewicz, Andrzej (Przestrzenie Teorii, 2007)
The subject of considerations in this work are Einstein's and Dirac's views on theoretical physics. Using as an example the Euclidean geometry and its epistemological status through the ages, the author outlines the basic philosophy of the modern theoretical physics, emphasising in particular the prominent role of ideas of simplicity and beauty as the guiding principles of research in theoretical physics.